Associação entre soropositividade para Toxoplasma gondii e desenvolvimento escolar de crianças atendidas em hospital público, Paraná, Brasil - Ferreira, Érika Cristina (2012)
The toxoplasmosis etiological agent known as T. gondii can influence its hosts' behavior. Both men and women who are seropositivity to T. gondii showed a slowed reaction time to a stimulus, as well as a decreased ability to maintain concentration. The aim of this study was to evaluate the possible association between seropositivity to T. gondii and the scholar development of children being treated in a public hospital, Parana, Brazil. One hundred 6-13-year-old children who had used the public health service were investigated, selected with 95%reliability and a margin of error of 10%. The children were treated at the Hospital Municipal de Maringá Thelma Villanova, in the city of Maringá, state of Parana, Brazil. A blood sample of each child was collected for a serologic test of the following antibodies: IgG and IgM anti-T. gondii by using indirect immunofluorescence and capture ELISA, respectively. TheScholar Performance Test (SPT) of writing, arithmetic and reading was applied to each child, and the result was classified as high, median and poor. The person responsible for each child was questioned about the characteristics of life and their feeding behavior. The comparison of the results was carried out by using both, Fisher?s exact test and t-Student test by applying the Statistica 9.0, SAS 9.1 (Statistical Analysis System) and Open Epi 2.3.1 software. The prevalence of seropositivity to T. gondii among children was of 8%. An association between seropositivity to T. gondii and the scholar development in the mathematics subtest was observed. An association between fresh cheese consumption and the seropositivity to T. gondii was also observed. The children who lived in a per domicile area with exposed soil, sand or lawn were 9.116 times more likely to have the infection by T. gondii. The findings showed the need of educational programs to be applied to families and educators, the monitoring of recreation areas, and awareness on nutritional care as well.